1999
DOI: 10.1063/1.124121
|View full text |Cite
|
Sign up to set email alerts
|

A vertical cavity light emitting InGaN quantum well heterostructure

Abstract: A method is described for fabricating a vertical cavity light emitting structure for nitride semiconductors. The process involves the separation of a InGaN/GaN/AlGaN quantum well heterostructure from its sapphire substrate an its enclosure by a pair of high reflectivity, low loss dielectric mirrors to define the optical resonator. We have demonstrated a cavity Q factor exceeding 600 in initial experiments, suggesting that the approach can be useful for blue and near ultraviolet resonant cavity light emitting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 11 publications
2
39
0
Order By: Relevance
“…In this case the excitonic mode is too broad and at too low an energy to see polariton coupling effects. 5,6,9 The measured Q factors lie within the range of the best reported values ͑400-750͒ for similar MCs with double dielectric Bragg mirrors [7][8][9] but here the use of GaN substrates with low threading dislocation densities gives the added benefit of improved epitaxial quality. As will be apparent from the examples discussed, measurements at different points on the two MCs produced significantly different PL spectra.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…In this case the excitonic mode is too broad and at too low an energy to see polariton coupling effects. 5,6,9 The measured Q factors lie within the range of the best reported values ͑400-750͒ for similar MCs with double dielectric Bragg mirrors [7][8][9] but here the use of GaN substrates with low threading dislocation densities gives the added benefit of improved epitaxial quality. As will be apparent from the examples discussed, measurements at different points on the two MCs produced significantly different PL spectra.…”
supporting
confidence: 74%
“…5,6 The so-called fully hybrid approach exploits the well-established properties of high-reflectivity dielectric DBRs for both upper and lower mirrors, and offers the potential for higher finesse MCs. [7][8][9][10] Fabricating a MC of this type requires accessing the underside of the active region by removal of the substrate and buffer layers. Laser lift-off ͑LLO͒ from a sapphire substrate, 7,8 plasma etching of a SiC substrate, 9 and wet chemical etching of a silicon substrate 10 have all been employed to achieve this.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These cracks in DBR could result in the reduction of reflectivity and increase in scattering loss. Recently, several groups have reported optically pumped GaN-based VCSELs mainly using three different kinds of vertical resonant cavity structure forms: (1) monolithic grown vertical resonant cavity consisting of epitaxially grown III-nitride top and bottom DBRs (all epitaxial DBR VCSEL), (2) vertical resonant cavity consisting of dielectric top and bottom DBR (dielectric DBR VCSEL), and (3) vertical resonant cavity consists of an epitaxially grown III-nitride top DBR and a dielectric DBR (hybrid DBR VCSEL) [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…The emission linewidth significantly decreased from 2.5 to 0.1 nm after the threshold condition. Thereafter, Song et al demonstrated a VCSEL structure consisting of InGaN multiple quantum wells (MQWs) and ten-pair SiO 2 /HfO 2 top and bottom DBR by using laser lift-off technology [19]. Since the reflectivity of top and bottom DBRs were 99.5% and 99.9%, respectively, the cavity Q-factor is larger than 600 in their experiments.…”
Section: Introductionmentioning
confidence: 99%